(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
3rd century BCE India saw in Aśoka a legendary emperor, widely admired for his political achievements but even more so for his unprecedented humanitarian approach to governance, which was deeply shaped by the Buddhist faith he adopted. His outstanding historical example invites a closer investigation into his character and behaviour patterns in the search for a new role model of cross-cultural leadership excellence. In this work I will contrast the leadership approaches of today which are strongly influenced by the Western academic world with the holistic, human-centred way we can extract from Buddhist teachings. From there I will examine Aśoka’s biography and character, as far as we can reinterpret from the available historical material, to extract in what manner and how closely he embodied the Buddhist ideal of leadership. To do so, I will as far as possible make use of archeologic evidence available in the form of epigraphs issued by the emperor. In this way, I hope to inspire leaders, Buddhists or non-Buddhists, to consider and embrace a leadership style which is felt most suitable for a globalised world we live in.